Lipid peroxidation and antioxidants in plasma and red blood cells from patients with pemphigus vulgaris - Naziroglu, Mustafa; Kökçam, Ibrahim; Şimşek, Halil; Karakilçk, A. Ziya (My University, 2003)
In pemphigus vulgaris, the increased production of reactive oxygen species from activated neutrophils decreases concentrations of antioxidant vitamins and enzymes in plasma and red blood cells (RBC), resulting in oxidative stress. We compared lipid peroxidation, a measure of reactive oxygen species production, antioxidant vitamins, reduced glutathione (GSH), glutathione peroxide (GSH-Px), and catalase enzyme activity in blood samples obtained from 18 nonsmoking pemphigus vulgaris patients and an equal number of age-and gender-matched, healthy control subjects. Plasma and RBC lipid peroxidation levels (malonyl dialdehyde) were significantly higher (p < 0.05) in pemphigus vulgaris patients than in control subjects. Significantly lower concentrations of plasma antioxidant vitamins (vitamin E and beta-carotene) and vitamin A (p < 0.001), antioxidant enzymes (catalase in RBC and plasma, GSH-Px in RBC [p < 0.05]), and respective GSH activities in both RBC and plasma (p < 0.05 and p < 0.01) were found in pemphigus vulgaris patients than in control subjects. GSH-Px in plasma did not change significantly. The results provide evidence for a potential role of increased lipid peroxidation and peroxidation and decreased antioxidants in pemphigus vulgaris by its inflammatory character. © 2011, by Walter de Gruyter GmbH & Co. All rights reserved.
Keywords: beta-carotene; catalase; glutathione peroxide; vitamin A; vitamin E